Pull-down Heller myotomy improves the clinical outcome of advanced sigmoid achalasia - Méndez-Hernández, Dulce Paola; Moreno-Fuentes, Miguel; Barron-Cervantes, Natalia Maria; Stenner-Escalante, Andres; Morales-Herrera, Carlos Alejandro; Aguilar-León, Diana; López-Mosqueda, Luis Gerardo; Romero-Osorio, Carlos Damián; Coss-Adame, Enrique; Valdovinos, Miguel A.; Valdovinos-García, Luis Raúl; Furuzawa-Carballeda, Janette; et al. (Springer Science and Business Media LLC, 2025)
Introduction: Esophagectomy was considered the first line for advanced sigmoid (aSg) achalasia (esophageal angulation < 90°), while laparoscopic Heller myotomy (LHM) has a lower percentage of success. The pull-down LHM (PD-LHM) technique has emerged as a promising and more effective rescue therapy to avoid esophagectomy for aSg achalasia. However, the long-term functional results of PD-LHM are inconclusive. Objective: To compare the outcome of aSg achalasia (< 90°) who underwent the PD-LHM technique with those of non-advanced (naSg) achalasia (≥ 90°) and LHM. Patients and methods: This ambispective nested cohort study evaluated 34 achalasia patients with megaesophagus divided into two groups: (a) aSg (< 90°; n = 20; 59%) PD-LHM treated, and (b) naSg (≥ 90°; n = 14; 41%) LHM treated. The assessments included esophageal angulation and symptom questionnaires. All patients were clinically and manometrically evaluated before and at 1- and 12-month post-surgery intervals. Clinical outcomes focused on achieving esophageal angulation ≥ 90° and an Eckardt score < 3. Results: 65% of patients were men, and 65% had achalasia type I. The mean esophageal angulation in aSg was 79.6 ± 8.8°, and in naSg was 116.3 ± 16.3°. aSg improved to 99.5 ± 15.2°, and 17/20 patients (85%) shifted to the naSg group. aSg significantly improved in Eckard symptom score at 1 month (1.2 ± 1.3) vs. preoperative score (8.9 ± 1.6). The three aSg patients who experienced PD-LHM failure were male, type I achalasia, had higher preoperative IRP and LES pressure, were older, and had longer disease duration vs. success. A good clinical and manometric outcome was obtained in 85% of aSg. Conclusion: Our findings suggest that PD-LHM is an effective treatment for aSg with a success rate of 85%. ©The authors ©Surgical Endoscopy ©Springer Science and Business Media LLC.
Keywords: Advanced sigmoid esophagus; Pull-down Heller myotomy; End-stage achalasia; Achalasia surgical treatment